2024
DOI: 10.1101/2024.06.30.601416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial transcriptomics reveals influence of microenvironment on intrinsic fates in melanoma therapy resistance

Ryan H Boe,
Catherine G Triandafillou,
Rossana Lazcano
et al.

Abstract: Resistance to cancer therapy is driven by both cell-intrinsic and microenvironmental factors. Previous work has revealed that multiple resistant cell fates emerge in melanoma following treatment with targeted therapy and that, in vitro, these resistant fates are determined by the transcriptional state of individual cells prior to exposure to treatment. What remains unclear is whether these resistant fates are shared across different genetic backgrounds and how, if at all, these resistant fates interact with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous results from our lab have shown that resistant colonies can come in multiple resistant types 20,34 , raising the possibility that the frequency of these different resistant types was different in the low-to-high-dose switch condition as compared to high or low dose alone. To assess this possibility, we used FateMap (see Goyal et al 2023 for more details) to quantify transcriptional heterogeneity across resistant colonies in all three conditions (Supp.…”
Section: Dose Escalation Demonstrates Cellular Adaptation During the ...mentioning
confidence: 93%
See 1 more Smart Citation
“…Previous results from our lab have shown that resistant colonies can come in multiple resistant types 20,34 , raising the possibility that the frequency of these different resistant types was different in the low-to-high-dose switch condition as compared to high or low dose alone. To assess this possibility, we used FateMap (see Goyal et al 2023 for more details) to quantify transcriptional heterogeneity across resistant colonies in all three conditions (Supp.…”
Section: Dose Escalation Demonstrates Cellular Adaptation During the ...mentioning
confidence: 93%
“…2C-D). At the same time, it is important to note that the fact that resistant cells can adopt different fates at low and high doses means that at least some degree of extrinsic conditions affect the ultimate state of the cell 34 , suggesting some degree of a programmed response as well as an encoding based on the initial state of the cell (see Discussion).…”
Section: Dose Escalation Demonstrates Cellular Adaptation During the ...mentioning
confidence: 99%